Incertidumbre, volatilidad y comovimientos en mercados de valores: un análisis del efecto contagio de crisis financieras internacionales (2020)
This article identifies the contagion effect of the global financial crisis (GFC) and the euro zone crisis (EZC) in 20 advanced economies and 25 emerging economies, in addition to studying risk transmission among economies during the COVID-19 crisis. Contagion is defined as an increase in correlations between markets during crisis periods. Using daily data between 2004 and 2020 from the MSCI index, the DCC-GARCH model is used to estimate correlations between stock market returns from each country and two sources of contagion (United States and Europe). The results suggest that Asian emerging countries were the most resilient to the contagion of the GFC and the EZC. These countries stood out for the implementation of macroprudential policies that decreased their vulnerability to external shocks. Finally, after isolating the volatility of macroeconomic fundamentals from the contagion test, evidence of risk transmission from the United States and Europe to other markets was found during the COVID-19 crisis, explained by panic in an environment of uncertainty.